Porous amphiphilic biogel from a facile chemo-biosynthetic route - Syed Mohamed, Syed Mohammad Daniel; M. Annuar, M. Suffian; Heidelberg, Thorsten; Ansari, Nor Faezah; Ismail, Nor Hidayah (Serbian Chemical Society, 2020)
Grafting of medium-chain-length poly-3-hydroxyalkanoates (mcl-PHA) with glycerol 1,3-diglycerolate diacrylate (GDD) in acetone was performed using benzoyl peroxide as the initiator. A detailed mechanism scheme provides significant improvement to previous literature. Radical-mediated grafting generated α–β carbon inter-linking of mcl-PHA and GDD, resulting in a macromolecular structure with gel properties. The thermal properties of the copolymer for different graft yields were investigated as a function of initiator concentration, GDD monomer concentration, incubation period and temperature. The water absorption and porosity of the gel were significantly improved relative to neat mcl-PHA.